1983
DOI: 10.2307/40166770
|View full text |Cite
|
Sign up to set email alerts
|

The Native Forest Birds of Guam

Abstract: JSTOR is a not-for-profit service that helps scholars, researchers, and students discover, use, and build upon a wide range of content in a trusted digital archive. We use information technology and tools to increase productivity and facilitate new forms of scholarship. For more information about JSTOR, please contact support@jstor.org.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
71
1

Year Published

1990
1990
2022
2022

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 57 publications
(75 citation statements)
references
References 17 publications
3
71
1
Order By: Relevance
“…Micronesian starlings (Aplonis opaca) are the only other frugivorous vertebrates on the atoll, but they feed primarily on smaller fruit and fruit with smaller seeds (Baker, 1951;Jenkins, 1983). Coconut crabs (Birgus latro) feed on fallen fruit (Reyne, 1939;Holthuis, 1963) and may rival Pteropus as seed dispersal agents for some island tree species, but this aspect of crab biology is poorly understood (Wiles et al, 1991).…”
Section: Status: In March 1986 Wiles Et Al (1991) Surveyed 14 Islandsmentioning
confidence: 99%
“…Micronesian starlings (Aplonis opaca) are the only other frugivorous vertebrates on the atoll, but they feed primarily on smaller fruit and fruit with smaller seeds (Baker, 1951;Jenkins, 1983). Coconut crabs (Birgus latro) feed on fallen fruit (Reyne, 1939;Holthuis, 1963) and may rival Pteropus as seed dispersal agents for some island tree species, but this aspect of crab biology is poorly understood (Wiles et al, 1991).…”
Section: Status: In March 1986 Wiles Et Al (1991) Surveyed 14 Islandsmentioning
confidence: 99%
“…However, observers noted that the birds nested in both termitaria and soft-wooded trees before their extirpation from Guam ( Jenkins 1983, Marshall 1989). Although we were unable to evaluate difference between the thermal characteristics of nest cavities constructed in wood and those in termitaria, cavities made in wood by Acorn Woodpeckers, Melanerpes formicivorus, and Northern Flickers, Colaptes auratus, have also been shown to provide protections from solar heat gain and convective and radiative heat losses (Hooge et al 1999, Wiebe 2001).…”
Section: Resultsmentioning
confidence: 99%
“…Micronesian Honeyeaters, along with most other native forest birds, were extirpated from Guam in the mid1980s with the arrival and range expansion of the brown treesnake (Boiga irregularis; Savidge 1987, Wiles et al 2003). Surveys on Rota, Tinian, and Saipan (the inhabited islands of the Commonwealth of the Northern Mariana Islands [CNMI]) have indicated that Micronesian Honeyeaters are less numerous on Saipan than on Rota or Tinian (Pratt et al 1979, Ralph and Sakai 1979, Jenkins and Aguon 1981, Jenkins 1983, Craig 1996 Engbring et al (1986) found that densities were greater on Saipan than on Tinian. On Saipan, Engbring et al (1986) counted 549 honeyeaters (mean of 2.25 birds per station Ϯ 0.14 SE), and estimated the total Micronesian Honeyeater population at 22,573.…”
mentioning
confidence: 96%